1980
DOI: 10.1044/jshd.4502.170
|View full text |Cite
|
Sign up to set email alerts
|

Planning an Initial Expressive Sign Lexicon for Persons with Severe Communication Impairment

Abstract: Selecting an initial sign lexicon for an individual requires far more than simply making a list of useful words or translating a spoken lexicon into signs through use of a sign dictionary. It requires knowledge of child language acquisition, knowledge of manual signs and linguistic constraints on their use, and knowledge of the needs and desires of the individual for whom the lexicon is intended. Suggestions of writers such as Holland (1975) and Lahey and Bloom (1977) are studied in terms of their appropriaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Few data-based studies are available (James, 1983(James, , 1985; however, a review of the AAC literature provides some guidance in the process of vocabulary selection. A number of authors have suggested guidelines for initial vocabulary selection (Blau, 1983;Carlson, 1981;Fristoe & Lloyd, 1980;Reichle, Williams, & Ryan, 1981). Although these authors focus primarily on vocabularies for linguistically developing individuals, many of their recommendations also apply to linguistically competent, nonspelling individuals.…”
Section: The Vocabulary Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Few data-based studies are available (James, 1983(James, , 1985; however, a review of the AAC literature provides some guidance in the process of vocabulary selection. A number of authors have suggested guidelines for initial vocabulary selection (Blau, 1983;Carlson, 1981;Fristoe & Lloyd, 1980;Reichle, Williams, & Ryan, 1981). Although these authors focus primarily on vocabularies for linguistically developing individuals, many of their recommendations also apply to linguistically competent, nonspelling individuals.…”
Section: The Vocabulary Selection Processmentioning
confidence: 99%
“…Care should be taken to expand the vocabulary beyond the selection of general items that simply reflect basic needs or beyond those items that may be more important to the caregivers than to the user. Even those authors, such as Fristoe and Lloyd (1980) who actually suggest a list of possible items that may be included in an initial lexicon, are careful to state that the process of selection is of primary concern and that how concepts are selected may be more 102 Yorkston, Honsinger, Dowden, and Marriner important than which items are selected. Another important consideration is the need to be responsive to the changing needs of the user.…”
Section: The Vocabulary Selection Processmentioning
confidence: 99%
“…It is generally decided that the vocabulary items for a child's first words should follow that of normally developing lexical acquisition as well as mold to the special needs of the child (Lahey & Bloom, 1977;Fristoe & Lloyd, 1980;Carlson, 1981). Lahey and Bloom (1977) outlined some critical areas involved in vocabulary selection.…”
Section: Strategies For Vocabulary Selectionmentioning
confidence: 99%
“…Regarding concept representation, although the American Sign Language (ASL) sign for more may be motorically easy to produce, it is not iconic, that is, it does not look like the concept it is representing (see Figure 1; Fristoe & Lloyd, 1980). When signs are iconic, they help children learn the meaning of words more easily.…”
mentioning
confidence: 99%